Examination of the interaction of parameters for low-intensity focused ultrasound of the human motor cortex - Areej Ennasr; Gabriel Isaac; Andrew Strohman; Wynn Legon (Brain Stimulation)
Background: Low-intensity focused ultrasound (LIFU) is a promising form of non-invasive neuromodulation characterized by a rich parameter space that includes intensity, duration, duty cycle and pulsing strategy. The effect and interaction of these parameters to affect human brain activity is poorly understood. A better understanding of how parameters interact is critical to advance LIFU as a potential therapeutic. Objective/hypothesis: To determine how intensity, duration, and duty cycle interact to produce neuromodulation effects in the human motor cortex. Further, this study assesses the effect of pulsing versus continuous ultrasound. We hypothesize that higher duty cycles will confer excitation. Increasing intensity or duration will increase the magnitude of effect. Pulsing LIFU will not be more effective than continuous wave ultrasound. Methods: N = 18 healthy human volunteers underwent 20 different parameter combinations that included a fully parametrized set of two intensities (ISPPA: 6 & 24 W/cm2), five duty cycles (1, 10, 30, 50, 70 %) and two durations (100, 500 msec) with a constant pulse repetition frequency of 1 kHz delivered concurrently with transcranial magnetic stimulation (TMS) to the primary motor cortex (M1). Four of these parameter combinations were also delivered continuously, matched on the number of cycles. Motor-evoked potential (MEP) amplitude was the primary outcome measure. All parameter combinations were collected time-locked to MEP generation. Results: There was no evidence of excitation from any parameter combination. 3 of the 24 parameter sets resulted in significant inhibition. The parameter set that resulted in the greatest inhibition (∼30 %) was an intensity of 6W/cm2 with a duty cycle of 30 % and a duration of 500 msec. A three-way ANOVA revealed an interaction of intensity and duty cycle. The analysis of continuous versus pulsed ultrasound revealed a 3-way interaction of intensity, pulsing, and the number of cycles such that under the 6W/cm2 condition higher cycles of pulsed ultrasound resulted in inhibition whereas lower number of cycles using continuous LIFU resulted in inhibition. Conclusions: LIFU to M1 in humans, in the range employed, either conferred inhibition or had no effect. Significant excitation was not observed. In general, lower intensity looks to be more efficacious for inhibition that depends on duration. In addition, pulsed ultrasound looks to be more effective for inhibition as compared to continuous wave after controlling for total energy delivered. Non-specific auditory effects may contribute to these results.